Contested grounds : essays on nature, culture, and power - Baviskar,Amita(Editor) (Oxford University Press, 2008)
Contributed articles presented earlier at a conference held at Kathmandu in 2003; later serialized in the Economic and political weekly on political aspects of natural resources.